PENGEMBANGAN KEMAMPUAN EKSPRESI PERAN SISWA DALAM PENANAMAN NILAI-NILAI AGAMA DI TK NURUL ISLAM KUDUS - Helina Himmatul’ Ulya Lina (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2019)
The results of the study are as follows: (1) the development of the ability to play the role of students in Nurul Islam Kindergarten, is to invite more students to be sociodrama and role play to express all feelings, words and actions. (2) Development of ability to support students in managing religious values in Nurul Islam Kindergarten, are students who can express play games such as compilation when visiting how to support good greetings, creating a shared environment, in sociodramas playing sellers and buyers not asking questions lying puts priority on the attitude of honesty, behaves well as we help friends who need our help, eating at meals together before and after eating requires it to pray. (3) Supporting Factors for the Development of Student Roles in Strengthening Religious Values in Nurul Islam Kindergarten, are teachers who always use creative ideas in the learning process so that they are more attractive to students and inefficient. In addition, the supporting factors are also provided by the teacher who provides a variety of games, explanations that are easy to discuss, adequate infrastructure, the comfort of a safe and pleasant environment, as well as parental participation and sanctions. (4) Looks better than those in Nurul Islam Kindergarten, are students in development who were less polite now students can be more polite, than those who are difficult to communicate with now can communicate well and quickly, socializing by prioritizing honesty, compassion, who had been shy but now can challenge to emerge, who was insensitive but now can be sensitive to his feelings and emotions. This is a characteristic in Nurul Islam Kindergarten that does not require learning related to abilities that support the role in managing religious values.